2008
DOI: 10.1097/gme.0b013e318168f09b
|View full text |Cite
|
Sign up to set email alerts
|

Beyond frequency

Abstract: Objective Most menopausal women report vasomotor symptoms (hot flashes, night sweats). However, not all women with vasomotor symptoms, including frequent symptoms, are bothered by them. The primary aim was to identify correlates of vasomotor symptom bother beyond symptom frequency. Design The Study of Women’s Health Across the Nation participants reporting vasomotor symptoms at annual visit 7 comprised the sample (N = 1,042). Assessments included hot flash and night sweats frequency (number per week) and bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(95 citation statements)
references
References 41 publications
4
89
2
Order By: Relevance
“…This finding supports those of Thurston and colleagues who found that negative affect, a construct related to neuroticism, was a strong predictor of “hot flash bother” and that women who were symptomatic for hot flashes but not bothered by them had low levels of negative affect. 59 However, among the PMI women with vasomotor symptoms in our study, neuroticism was not related to level of interference from the hot flashes/sweats, nor was it related to number of these symptoms. Possibly, some mediating or moderating factor other than neuroticism that is unique to the PMI women causes more bother due to hot flashes.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This finding supports those of Thurston and colleagues who found that negative affect, a construct related to neuroticism, was a strong predictor of “hot flash bother” and that women who were symptomatic for hot flashes but not bothered by them had low levels of negative affect. 59 However, among the PMI women with vasomotor symptoms in our study, neuroticism was not related to level of interference from the hot flashes/sweats, nor was it related to number of these symptoms. Possibly, some mediating or moderating factor other than neuroticism that is unique to the PMI women causes more bother due to hot flashes.…”
Section: Discussioncontrasting
confidence: 73%
“…In fact, insomnia itself may affect perceived bother of vasomotor symptoms. 59 Our findings need to be considered in light of study limitations. Our study is cross-sectional, therefore, direction of causality cannot be determined.…”
Section: Discussionmentioning
confidence: 90%
“…Women with greater BMI had longer total VMS duration, broadly consistent with other findings from SWAN indicating a greater likelihood of reporting hot flashes with higher adiposity. 5,15 However, BMI was no longer significantly associated with total VMS duration herein in multivariable models when considering factors such as race/ethnicity.…”
Section: Discussionmentioning
confidence: 90%
“…4,5,4043 Pathways connecting negative affective factors and VMS are likely complex and bidirectional. 15,4446 A direct physiological link through the hypothalamic-pituitary-gonadal axis between negative affective factors and VMS has been proposed 47 but is not well tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation